HUBUNGAN KETERAMPILAN MEMBACA TERHADAP KETERAMPILAN MENULIS NARASI SISWA KELAS IV DI SDN 26 CAKRANEGARA - ZAKIA, ZAKIA; MUSADDAT, SYAIFUL; INDRAWATI, DYAH; MAKKI, MUHAMMAD (LEARNING : Jurnal Inovasi Penelitian Pendidikan dan Pembelajaran, 2024)
This research aims to uncover the correlation between reading skills and narrative writing skills among fourth-grade students at SDN 26 Cakranegara. Data collection was conducted using tests that measure reading and narrative writing skills. The tests involved asking questions or assigning tasks to students. To determine the correlation between reading and narrative writing skills, the data was analyzed using the product moment correlation. Before this, a descriptive analysis of the researched variables is presented. Descriptive analysis was conducted to understand the relationship between reading and narrative writing skills among students at SDN 26 Cakranegara. Data on reading skills were obtained from a closed questionnaire distributed to 75 students. The questionnaire contained 27 statements with a score range of 1 to 4 for each statement, giving a total score range of 27 to 108 for reading skills. Using SPSS 23.0 for Windows, the mean score was 91.6, the maximum score was 107, the minimum score was 75, and the standard deviation was 7.4. The classification of reading skills based on the mean and standard deviation is presented in a table. Data on narrative writing skills were obtained from a writing test, evaluated on several aspects including ideas, content organization, grammar, diction, spelling, and writing conventions. The scores ranged from 0 to 100. The mean score was 50, the maximum score was 100, and the standard deviation was 16.7. The classification of narrative writing skills is presented in a table. ABSTRAKPenelitian ini bertujuan untuk mengungkapkan korelasi antara keterampilan membaca dan keterampilan menulis narasi siswa SDN 26 Cakranegara. Pengambilan data dilakukan dengan menggunakan tes yang mengukur keterampilan membaca dan menulis narasi. Tes dilakukan dengan memberikan angket dan tugas kepada siswa. Untuk mengetahui korelasi antara keterampilan membaca dan menulis narasi, data dianalisis menggunakan korelasi product moment. Sebelum itu, analisis deskriptif dari variabel penelitian disajikan. Analisis deskriptif dilakukan untuk mengetahui hubungan antara keterampilan membaca dan keterampilan menulis narasi siswa SDN 26 Cakranegara. Data keterampilan membaca diperoleh dari angket tertutup yang dibagikan kepada 75 siswa. Angket terdiri dari 27 pernyataan dengan rentang skor 1 sampai 4, sehingga total skor berkisar antara 27 sampai 108. Menggunakan SPSS 23.0 for Windows, nilai mean adalah 91,6, skor maksimal 107, skor minimal 75, dan standar deviasi 7,4. Klasifikasi keterampilan membaca berdasarkan mean dan standar deviasi disajikan dalam tabel.